The madness of 'The Murderess' - Menelaou, Iakovos (Research and Humanities in Medical Education, 2019)
This paper discusses Alexandros Papadiamantis' (1851-1911) novel 'The Murderess' and analyses the protagonist's (Hadoula or Frankojannou) psychological state and the reasons behind her actions to murder girls. Papadiamantis' protagonist does not compromise on her role in society and the 'superiority' of men in a man-made world, but, beyond the obvious, she is not a typical old woman. Reading through the book from the perspective of the medical humanities shows that Hadoula suffers from mental health problems, which make her see the murders she commits as a reasonable reaction to protect girls from the injustices of a patriarchal society. Papadiamantis gives the portrait of a 'serial killer', who has almost convinced herself that these murders constitute an ethical action. Although a fictional account, the book allows one a glimpse into mental illness from the perspective of the person who is ill.